(untitled) (UNIZIK Journal of Marketing, 2025)
This study examined the determinants of consumer hotel selection in Enugu state, Nigeria. Specifically, the study aimed at exploring the effects of hotel attributes including hotel location, service quality, hotel facilities, price of hotel services, and guest security on consumer hotel selection in Enugu state, Nigeria. The study was quantitative in nature and correlational design. The population size was unknown while the sample size was 384. The study used a quota sampling technique in reaching the respondents. The instrument of data collection was a structured questionnaire. The validity of the instrument was tested using expert opinion while the reliability of the research instrument was tested using Cronbach Alpha coefficient. Multiple regression statistical analysis method was used to test the formulated hypotheses at 5% level of significance. The findings revealed that hotel location, service quality, hotel facilities, price of hotel services, and guest security have significant effect on consumer hotel selection in Enugu state, Nigeria.The study recommended that hotel managers in Enugu state Nigeria should considers building hotels in convenient locations, offering quality hotel services, utilizing quality hotel facilities, offering services at competitive prices and ensuring provision of adequate security infrastructure in order to improve consumer’s selection of their hotels.The implication of this is that management of hotels in Enugu state, Nigeria should effectively coordinate all hotel attributes especially those understudy for effective customer services delivery to ensure consumer selection of their hotels.